Evaluation of Thermal Comfort in Jamik Mosque Lhokseumawe - Muhammad Iqbal; Tjut Nashiha Tsany; Eri Saputra; Effan Fahrizal (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
To serve a solemn praying condition for worshippers, most of the mosques currently install Air Conditioning (AC). Jamik Mosque Lhokseumawe, as one of the mosques that have the AC, becomes a research site. The purpose is to see levels of thermal comfort in the mosque based on ASHRAE-55 standards, which mainly studies the main praying area using AC and the mosque porch with no AC. This study applies a quantitative method and calculations with a Predicted Mean Vote (PMV). The results of mean measurements at Dzuhur time showed the highest temperature, in which at the main praying area is 29.5oC with 52.2% humidity and at the mosque porch is 32.1oC with 62.0% humidity. Even though the result showed PMV value of 1.67 at the main praying area and 2.18 at the mosque porch, which is categorized as warm, but the survey results showed that respondents still felt comfortable. It is due to some respondents’ familiarity with the temperature. The results conclude that the available Air Conditioning has not created the mosque areas as a comfortable place.